Megacólon secundário a avulsão da base da cauda em um cão. - Silva, Sanderleia Leal (Universidade Federal do Tocantins, 2023)
The supervised internship was developed at the Veterinary University Clinic of the Veterinary School of Medicine and Animal Science at the Federal University of Tocantins, under the supervision of the veterinarian André Rolim Monteiro and the guidance of Prof. Dr. Tiago Barbalho Lima, held from March 6th to May 25th, 2017, within a total of 420 hours. During this internship, it had been followed clinical cases in the Clinical and Surgical area of Small Animals, being made participation in clinical and outpatient services, as well as surgical procedures, including pre, trans and postoperative procedures. Besides the monitoring and administration of medications in patients who remained hospitalized. There were followed 72 clinical cases and 37 surgical cases, described in the course of this paper through figures, tables and graphs. The purpose of this report is to describe the activities carried out during the internship, addressing the casuistry followed during it, and to report a clinical and surgical case in a canine patient, no defined breed, 12 years old, 20.6 kg, presenting megacolon associated with fecaloma, secondary to base avulsion of the tail, which was submitted with a subtotal colectomy as its treatment.